A Conceptual Review of Amlapitta w.s.r to Gastro-Esophageal Reflux Disease - Rout, Diptimayee; Panda, Pradeep Ku; Nayak, Utkalini; Biswal, Ambuja Kumar (International Research Journal of Ayurveda & Yoga, 2022)
Today due to modern life style and food habits most of the population is suffering from a common disease called as Amlapitta. Amlapitta is a result of inappropriate dietary regimen or stress. Amlapitta is one of the commonest diseases of Annavaha srotas (Gastrointestinal tract) caused by vitiated Agni. Here in this present paper Amlapitta disease is reviewed in detail according to Ayurvedic view and Modern view. Amlapitta is a condition where Amlaguna (Sour Taste) of Pachak pitta (gastric Juice) increases due to Samata. Amlapitta has been considered as Pitta pradhana Tridoshaja Vyadhi (compound disease caused by multiple factors). Aacharya Kashyapa has mentioned as the involvement of three Doshas in Amlapitta while Madhavkara has mentioned that the pitta is dominant in this disease.